PENGARUH KEBIASAAN BELAJAR SEKOLAH TERHADAP HASIL BELAJAR EKONOMI SISWA XI IPS SMAN 6 PONTIANAK - Kurnia, Kessy; Purwaningsih, Endang; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to find out the effect of study habits in school on the students? learningoutcomes in the Economic subject of class XI IPS SMAN 6 Pontianak. This study wasconducted in the form of correlational research, of which the data were presentedquantitatively. The sample of this study was 70 students of class XI IPS at SMAN 6Pontianak. Data were collected using questionnaires, of which the validity andreliability had been tested. The data were analyzed using simple linear regression testwith SPSS version 18.00. The finding showed that the students learning habits, ingeneral, was in the medium category by 70%. Based on the analysis, obtained theequation Y = 14.375 + 0,845X. The t-test showed the value of tcount>ttable (3.175 >1.995), meaning that Ho was rejected and Ha was accepted. The coefficient ofdetermination (R2) by 0,254 showed that the percentage of the effect of learning habitsin school on the students? learning results on the Economic subject of class XI IPSSMAN 6 Pontianak was 25.4%, and the rest 74.6% was influenced by other factorswhich were not examined in this study.Keywords:Lerning Habits in School, Students Learning Outcomes